1997
DOI: 10.1007/s003359900504
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the porcine myogenin gene locus

Abstract: Abstract. The myogenin (MYOG) gene fulfills a key function in muscle differentiation by controlling the onset of myoblast fusion and the establishment of myofibers. In meat-producing animals like pigs and cattle, myofiber numbers have been related to growth capacity. We have characterized the porcine MYOG gene to detect genetic variation at this locus and to relate it to growth characteristics. MYOG gene fragments were isolated by PCR on genomic DNA and by screening a genomic library with a mixture of the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 33 publications
3
52
0
Order By: Relevance
“…Genetic influence of the MRF gene family on porcine muscle development has been shown before. Genetic variation in porcine myogenin was related to muscle and general body growth (Soumillion et al, 1997;te Pas et al, 1999a ) while myf-5 did not show such a relationship (te Pas et al, 1999b ). Furthermore, postnatal expression levels of myf-5, MyoD, and myogenin were related to growth rate (te Pas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic influence of the MRF gene family on porcine muscle development has been shown before. Genetic variation in porcine myogenin was related to muscle and general body growth (Soumillion et al, 1997;te Pas et al, 1999a ) while myf-5 did not show such a relationship (te Pas et al, 1999b ). Furthermore, postnatal expression levels of myf-5, MyoD, and myogenin were related to growth rate (te Pas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the expectations resulting from previously published studies (Verner et al, 2007;Civaňova and Knoll, 2007;Stupka et al, 2012) all of the MYF4 genotypes showed only non-significant (P<0.05) impact on selected production traits. The associations of MYOD genes family with pork quality has been previously investigated in various pig populations by several studies (Soumillion et al, 1997;Kapelañski et al, 2005;Cinar et al, 2012;Stupka et al, 2014). The MyoD genes were tested as candidate genes with an expected, significant effect principally on the muscle deposition (Kłosowska et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the concentration and purity of genomic DNA were analysed based on the spectrophotometry measurements by the optical density at wave length of 260 nm. The polymorphism in MYF4 gene was analysed according to Soumillion et al (1997) using restriction endonuclease MspI. The products of PCR reaction and restriction fragments have been separated and visualised using horizontal electrophoresis in 2% agarose gels (130 V for 50 min) and stained with day GelRed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations